Chapter La libertà viene prima. La libertà come posta in gioco nel conflitto sociale - Trentin, Bruno (Studi e saggi, 2021)
What is left of socialism ? This question, too, must be answered in a "project left." Certainly, socialism is no longer an accomplished or well-known model of society to tend tothrough daily political action. It can only be conceived as an uninterrupted search for the liberation of the person and his capacity for self-realization. It should be possible introducing elements of socialism into concrete society such as: equal opportunities, community welfare, control over the organization of work, the diffusion of knowledge as an instrument of freedom. This would overcome, from time to time, the contradictions and failures of capitalism and the market economy, making the person, and not only the classes, the keystone of civil coexistence. (From the cover of the first edition).